MESIN ROLL BENDING PLAT AKRILIK - Fauzi, Alfan; Ayu Wardani, Angelia Hermiati; As’adi, Hasan; Husodo, Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Acrylic cylinder is a component that is commonly used as a reactor in the addition process, which is mixing several types of chemicals. Because mixing chemicals corrode the container usually used, so use of the acrylic. In a small industrial establishment acrylic cylinder still use manually way, which is preheated using welding acytelin then performed bending process. This causes low quality products because the products produced corrugated surface due uneven heating and work safety are minimal. Therefore, in require of a machine that can solve the problem, to produce smooth cylindrical surface isnât corrugated. These machines are designed using a three-roll system that is placed in a triangle and the heaters are placed in between the two roll below, so that the plate can be bent straight up in preheat plate ready to be bent. Thus producing smooth surface and is expected to support the engine production capacity of small industries. From the calculation power needed 0.17 HP motor, the motor rotation 1500 rpm is reduced by a gearbox with a ratio of 1:50 to drive two 60 mm diameter roll with a speed of 30 rpm and from the calculation power needed 133 W electrical heater. After testing, it was found that the product quality is better acrylic cylinder with no waves on the surface.Keyword : Roll Bending Machine, Heater, Acrylic.